The Correlation between Verbal Linguistic Intelligence and Reading the Qur'an in an Islamic Perspective - Septi Gumiandari; Ayu Sabrina; Ilman Nafi'a (CV. Tripe Konsultan, 2023)
The reality that still occurs among students is that they cannot read the Qur'an fluently. It is not surprising that there are students who respond slowly in learning the Qur'an. This study aims to determine the accuracy between verbal-linguistic intelligence and reading the Qur'an. The authors use a theoretical descriptive method with content analysis techniques by quoting several opinions according to experts and according to an Islamic perspective. The discussion results show that students with verbal-linguistic intelligence can know the laws of recitation (tajwid), read the Qur'an fluently and easily memorize the Qur'an. Even easily write verses of the Qur'an, poems or other essays than students who do not have linguistic-verbal intelligence.